[PP.04.17] ADDITIONAL FACTORS THAT MAY HELP IN LV DIASTOLIC FUNCTION ASSESSMENT. (September 2017) - Torbas, O.; Sirenko, Y.U.; Radchenko, G.; Rekovets, O.; Granich, V.; Kushnir, S.; Dobrokhod, A.; Sidorenko, P.; Polischuk, S.
Abstract : Objective: Increased arterial stiffness may cause increased LV stiffness that may influence LV diastolic function (DF) and could be used also for LF DF assessment. Design and method: We included 61 patients with moderate to severe AH. We performed office BP (oBP) and heart rate (HR) measurements, ambulatory BP monitoring, central systolic BP (cSBP), augmentation index (Aix@75) and PWV measurement, CAVI index and ankle-brachial index (ABI) measurements. Echocardiography was performed according to local protocol with measurements of peak E velocity, peak A, the E/A ratio, peak E' and E/E' ratio, deceleration time (Dt), isovolumetric relaxation time (IVRT), LV myocardium mass index (LVMMI) evaluated with the ASE formula, ventricle-arterial coupling (VAC) was evaluated according to standard method. To find interactions we used Spearman correlation analysis. Results: Mean characteristics: BMI 29, 6 ± 0, 7 km/m 2, mean age 53, 6 ± 1, 9 years, men/women 53/47%, oSBP 158, 8 ± 3, 4 mmHg, oDBP 95, 3 ± 2, 2 mmHg, oPBP 61, 3 ± 2, 9 mmHg, HR 79, 1 ± 2, 5 beats/min, 24hSBP 146, 0 ± 2, 3 mmHg, 24hDBP 89, 5 ± 1, 8 mmHg, 24hPBP 60, 1 ± 3, 5 mmHg, cSBP 130, 4 ± 3, 7 mmHg, cDBP 87, 2 ± 2, 0 mmHg, cPBP 44, 2 ± 2, 8 mmHg, PWV 11, 8 ± 0, 5 m/s, CAVId 8, 5 ± 0, 3, CAVIs 8, 4 ± 0, 3, LVMMI (w/m) 91, 9 ± 3, 5 (86, 7 ± 1, 9 / 97, 7 ± 1, 6) g/m 2, E/A 1, 2 ± 0, 2, E/E' 7, 7 ± 0, 4 Dt 253, 2 ± 13, 4 ms, IVRT 90, 7 ± 5, 5 ms. E/A correlated with age (r = −0, 308), cPBP (r = −0, 44), augmentation pressure (r = −0, 513), Aix@75 (r = −0, 517), CAVId (r = −0, 575), CAVIs (r = −0, 558), EF (r = −0, 398), LVMMI (r = −0, 43), oPBP (r = −0, 335), p < 0, 05 for all. E/E' correlated with ejection duration (r = −0, 56), cDBP 0, 477, cPBP 0, 409, SEVR 0, 468, oPBP 0, 6, LVMMI 0, 345, CAVId 0, 41, CAVIs (r = 0, 406), p < 0, 05 for all. Dt correlated with end-diastolic volume (r = 0, 346), cDBP (r = −0, 31), ABI (r = 0, 616) and IVRT correlated with ABI (r = 0, 616), VAC (r = 0, 346), p < 0, 05 for all. Conclusions: Indicators of LV DF significantly associated with indicators of pulse wave analysis and arterial stiffness that can be used in routine clinical practice for the earliest diagnosis of early progression of diastolic dysfunction.